Theoretical and practical difficulties in regulating insider trading in South Africa and possible mechanisms of improvement of shortcomings in the regulatory framework - Botha, Monray Marsellus (University of Pretoria, 2020)
Mini Dissertation (LLM (Corporate Law))--University of Pretoria, 2020.